2023
DOI: 10.1177/10731911231165071
|View full text |Cite
|
Sign up to set email alerts
|

The Worry Behaviors Inventory–Perinatal Revised: Adaptation and Initial Validation for Use in Perinatal Samples

Abstract: Generalized anxiety disorder (GAD) is a leading mental health concern during pregnancy and the postpartum (perinatal) period. People with GAD engage in problematic behaviors to manage their distress. However, the extent of GAD behaviors during the perinatal period may not be adequately captured by the Worry Behaviors Inventory (WBI), the most comprehensive measure of GAD behaviors to date. We evaluated the structure of the initial WBI item-pool and then evaluated the internal consistency, construct validity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
0
0
0
Order By: Relevance
“…In related work, led by our graduate student Briar Inness, we found that worry behaviours associated with GAD in the perinatal period are also thematically differentiated from those in a nonperinatal sample (Inness et al, 2022). These findings formed the basis for adapting a measure to specifically assess perinatal worry behaviours: The Worry Behaviors Inventory—Perinatal Revised (Inness et al, 2024).…”
Section: Integration Of Clinical Services Research and Trainingmentioning
confidence: 99%
“…In related work, led by our graduate student Briar Inness, we found that worry behaviours associated with GAD in the perinatal period are also thematically differentiated from those in a nonperinatal sample (Inness et al, 2022). These findings formed the basis for adapting a measure to specifically assess perinatal worry behaviours: The Worry Behaviors Inventory—Perinatal Revised (Inness et al, 2024).…”
Section: Integration Of Clinical Services Research and Trainingmentioning
confidence: 99%